The Complex Interplay between Lipids, Immune System and Interleukins in Cardio-Metabolic Diseases. - Bernardi, Stella; Marcuzzi, Annalisa; Piscianz, Elisa; Tommasini, Alberto; Fabris, Bruno (Int J Mol Sci, 2018)
Lipids and inflammation regulate each other. Early studies on this topic focused on the systemic effects that the acute inflammatory response-and interleukins-had on lipid metabolism. Today, in the era of the obesity epidemic, whose primary complications are cardio-metabolic diseases, attention has moved to the effects that the nutritional environment and lipid derangements have on peripheral tissues, where lipotoxicity leads to organ damage through an imbalance of chronic inflammatory responses. After an overview of the effects that acute inflammation has on the systemic lipid metabolism, this review will describe the lipid-induced immune responses that take place in peripheral tissues and lead to chronic cardio-metabolic diseases. Moreover, the anti-inflammatory effects of lipid lowering drugs, as well as the possibility of using anti-inflammatory agents against cardio-metabolic diseases, will be discussed.
Keywords: Anti-Inflammatory Agents; Cardiovascular Diseases; Humans; Hypolipidemic Agents; Immune System; Inflammation; Interleukins; Lipid Metabolism; Lipids; Metabolic Diseases